Multi-component pharmacokinetic study of prunus mume fructus extract after oral administration in rats using UPLC-MS/MS - Zhu, Yameng; Wei, Shujie; Cao, Xiunan; Wang, Songrui; Chang, Yanxu; Ouyang, Huizi; He, Jun (Frontiers in Pharmacology, 2022)
Mume Fructus (MF) is a well-known traditional Chinese medicine (TCM) with the homology of medicine and food, and has a lot of pharmacological activities including antibacterial, antioxidant, antitumor, relieving thirst and antidiarrhea effects, etc. In the present study, a reliable and sensitive UPLC-MS/MS method has been developed and validated for the simultaneous determination of 16 bioactive compounds (L-(-)-malic acid, 3,4-Dihydroxybenzaldehyde, protocatechuic acid, vanillic acid, caffeic acid, D-(-)-quinic acid, citric acid, ferulic acid, syringic acid, cryptochlorogenic acid, neochlorogenic acid, chlorogenic acid, amygdalin, maslinic acid, corosolic acid and rutin) in rat plasma after oral administration of MF extract. The plasma samples were prepared by protein precipitate with acetonitrile. And the 16 active compositions were separated on an ACQUITY UPLC BEH C18 column (2.1 × 100 mm, 1.7 μm) with a gradient mobile phase system of methanol and 0.1% (v/v) formic acid aqueous solution at a flow rate of 0.3 mL/min. All active compositions were quantitated using Agilent Jet Stream electrospray ionization (AJS ESI) in a negative ion mode. The intra-day and inter-day accuracy ranged from -9.4% to 9.4%, and the precisions of the analytes were less than 14.8%. The extraction recoveries of the analytes were in the range of 63.59% to109.44% and the matrix effects ranged from 49.25% to 109.28%. Stability studies proved that the analytes were stable under the tested conditions, with a relative standard deviation (RSD) lower than 13.7%. The developed method was successfully applied to evaluate the pharmacokinetic study of 16 bioactive compositions after oral administration of MF extract in rat by UPLC-MS/MS.